STRATEGI INTEGERASI EKOWISATA BAHARI DAN KONSERVASI HUTAN WISATA NOSTALGIA DI KELURAHAN KABOLA, ALOR - Lisa Victoria Malimou; Marsalina Malaikari; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
This study analyzes sustainable management strategies in Kabola Subdistrict, Alor Regency, East Nusa Tenggara (NTT). The coastal area of Kabola (covering 5.069 km² with a population of 4,398) has dual potential as a coastal tourism destination characterized by scenic coastal attractions and as an economic base for fisheries as the main trading sector. Key fishery resources include tuna, belo-belo, and octopus. The primary objective of this study is to formulate an integrated utilization strategy model, in which the Nostalgia Tourism Forest (located in Buiko) is prioritized for the protection of vegetation and natural freshwater springs as key attractions, in alignment with the sustainable management of marine resources. Methodologically, this research employs a descriptive qualitative approach supported by analyses based on the Environmental Carrying Capacity theory (Ceballos-Lascuráin, 1996) and the Conservation Economy concept (UNWTO, 2005). The findings indicate that the recommended strategy is the integration of community-based governance and the diversification of marine ecotourism, which supports the subdistrict’s mission to enhance community welfare.